Paratanus exitiosus is a vector of the Fodder Beet Wilting Yellowing Phytoplasma (16SrIII-J) - Bongiorno, Vanina Aylén (2025)
“Yellow Wilt Disease” has emerged as a significant disease of Fodder Beet (YWD) in Argentina, affecting cattle feeding and causing substantial economic losses. This disease is attributed to phytoplasmas, a group of wall-less plant pathogenic bacteria, transmitted by phloem-feeding hemipteran insects. Given the challenges of managing diseases caused by systemic pathogens, effective control of vector insects is critical to reducing environmental impact and limiting disease spread. Therefore, the aim of this work was to identify insect vectors of YWD, and recognize accurately on the field the disease symptom. Field surveys were conducted in the Valle Medio and Valle Inferior regions of Rio Negro and Buenos Aires provinces. We report that Paratanus exitiosus (Beamer) is a vector of the fodder beet Yellow Wilt Disease in Argentina, caused by a 16Sr III, subgroup J phytoplasma, as demonstrated by experimental transmission assays. This finding, which will contribute to the design of more accurate disease management strategies in fodder beet crops, serves as a starting point for epidemiological and dynamic studies of other significant pathosystems involving 16SrIII-J group phytoplasmas, which have a notable impact on Argentina’s agriculture.